Free E-Collaboration Tools as a Support for Leading Virtual Teams - Vuorenmaa, Antti (2011)
Vuorenmaa, Antti Free E-Collaboration Tools as a Support for Leading Virtual Teams Jyväskylä: University of Jyväskylä, 2011, 29 p. Information Systems, Bachelor’s Thesis Supervisor(s): Seppänen, Ville This Bachelor's thesis is a study of the current freely available e-collaboration tools as solutions to problems of leading a virtual team. The research is conducted as a review of literature on the field of virtual teaming, with a brief overview of the tools available. There are three restrictions imposed on the research area: the technology is re-stricted to collaboration tools. This set of tools is further diminished by the start-up-entrepreneurial perspective, which dictates that the tools need to be available at no cost. Thirdly, the research only concentrates on the problems of a virtual team from the lead-ership perspective. The research question is "Do freely available e-collaboration tools solve the prob-lems of leading virtual teams?" The answer emerging from the research is "partly". This is because most of the identified problems could only be helped by the technology, not actually solved. The study consists of an introduction, a concept analysis, discussion of problems, a brief presentation of the e-collaboration tools along with feature descriptions, a de-scription of the solutions, and finally the conclusions. The main concepts in the research area are virtualness, group, virtual teams, lead-ership of virtual teams and e-collaboration. The most important conclusion of this study is that although the technology on its own will not solve the problems of leading a vir-tual team, it is a critical enabler.